Production of ϒ(nS) mesons in Pb + Pb and pp collisions at 5.02 TeV - Aad, Georges; Baltes, Lisa Marie; Bartels, Falk; Castillo, Florencia Luciana; Czurylo, Marta; Rio, Fernando del; Dittmeier, Sebastian; Dunford, Monica; Franchino, Silvia; Klassen, Martin; Krishnan, Anjali; Mkrtchyan, Tigran; et al. (Physical review, 2023)
A measurement of the production of vector bottomonium states, ϒ (1S), ϒ (2S), and ϒ (3S), in Pb + Pb and pp collisions at a center-of-mass energy per nucleon pair of 5.02 TeV is presented. The data correspond to integrated luminosities of 1.38 nb−1 of Pb + Pb data collected in 2018, 0.44 nb−1 of Pb + Pb data collected in 2015, and 0.26 fb−1 of pp data collected in 2017 by the ATLAS detector at the Large Hadron Collider. The measurements are performed in the dimuon decay channel for transverse momentum pμμ T < 30 GeV, absolute rapidity |yμμ| < 1.5, and Pb + Pb event centrality 0–80%. The production rates of the three bottomonium states in Pb + Pb collisions are compared with those in pp collisions to extract the nuclear modification factors as functions of event centrality, pμμ T , and |yμμ|. In addition, the suppression of the excited states relative to the ground state is studied. The results are compared with theoretical model calculations.
Gesehen am 18.11.2024
The ATLAS collaboration: G. Aad, L.M. Baltes, F. Bartels, F.L. Castillo, M.M. Czurylo, F. Del Rio, S. Dittmeier, M. Dunford, S. Franchino, M. Klassen, A. Krishnan, T. Mkrtchyan, P. Ott, D.F. Rassloff, S. Rodriguez Bosca, C. Sauer, A. Schoening, H.C. Schultz-Coulon, V. Sothilingam, R. Stamen, P. Starovoitov, L. Vigani, S.M. Weber, M. Wessels, X. Yue, J. Zinsser [und 2863 weitere]